Structure and function in rhodopsin: Packing of the helices in the transmembrane domain and folding to a tertiary structure in the intradiscal domain are coupled - Hwa, John (The National Academy of Sciences of the USA, 1997)
A previous study of the retinitis pigmentosa mutation L125R and two designed mutations at this site, L125A and L125F, showed that these mutations cause partial or total misfolding of the opsins expressed in COS cells from the corresponding mutant opsin genes. We now report on expression and characterization of the opsins from the following retinitis pigmentosa mutants in the transmembrane domain of rhodopsin that correspond to six of the seven helices: G51A and G51V (helix A), G89D (helix B), A164V (helix D), H211P (helix E), P267L and P267R (helix F), and T297R (helix G). All the mutations caused partial misfolding of the opsins as observed by the UV/visible absorption characteristics and by separation of the expressed opsins into fractions that bound 11-cis-retinal to form the corresponding mutant rhodopsins and those that did not bind 11-cis-retinal. Further, all the mutant rhodopsins prepared from the above mutants, except for G51A, showed strikingly abnormal bleaching behavior with abnormal metarhodopsin II photointermediates. The results show that retinitis pigmentosa mutations in every one of the transmembrane helices can cause misfolding of the opsin. Therefore, on the basis of these and previous results, we conclude that defects in the packing of the transmembrane helices resulting from these mutations are relayed to the intradiscal domain, where they cause misfolding of the opsin by inducing the formation of a disulfide bond other than the native Cys-110—Cys-187 disulfide bond. Thus, there is coupling between packing of the helices in the transmembrane domain and folding to a tertiary structure in the intradiscal domain.